Soft-power, culturalism and developing economies: the case of Global Ibsen - Huq, Sabiha (Humanities & social sciences communications, 2019)
This paper on soft-power connected with culturalism vis-à-vis Henrik Ibsen, draws its essence from the term ‘soft power’ coined and defined by Joseph S Nye Jr. and read in contiguity with ‘culturalism’ that Arjun Appadurai connotes as “identity politics mobilised at the level of the nation-state”. On these terms, the present author perceives ‘soft power’ as a force that affects or is expected to affect not just few specially endowed individuals in any given society; rather as one that works upon the mindscapes of the commoner, or in the collective unconscious. The quintessential social critic that inheres Ibsen the playwright, is here looked upon as such a reservoir of soft-power, whose dramatic oeuvre and its subsequent global reception have ignited ideas of social reform and thus have become part of Norwegian culturalism and soft power. While the Norwegian Government has funded projects and encouraged institutional collaborations in this connection, individuals too have taken up vital roles in establishing intercultural links using Ibsen as their ambassador. At present Ibsen is part of cultural exchange between Norway and many developing countries of Asia and Africa. What happens to the targeted receivers of such soft power is a valid question and this paper explores soft power from the perspective of the third world marginalised subject position. Dwelling upon specific channels of Norwegian soft-power that have proven world-wide currency, and the indefatigable ways in which Ibsen has been a major tool in such soft diplomacy, this paper attempts to analyse how Ibsen the dramatist has eventually become a significant part of Norwegian culturalism as soft power whose outreach is aimed at the egalitarian ideal, hence imbued with enormous potential to function as a strong influence in intercultural affairs.